2000
DOI: 10.1080/03079450050045477
|View full text |Cite
|
Sign up to set email alerts
|

The development and application of a blocking ELISA kit for the diagnosis of infectious coryza

Abstract: A blocking enzyme-linked immunosorbent assay (B-ELISA) kit for the diagnosis of infectious coryza was developed in this study. The kit was based on a recently described blocking ELISA that uses monoclonal antibodies to achieve specificity for antibodies to either Haemophilus paragallinaru m serovar A or serovar C. The results showed that the B-ELISA kit detected 96 and 90%, respectively, of chickens vaccinated or challenged with H. paragallinaru m serovar A. When used on chickens vaccinated or challenged with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Blocking ELISA, a specific method for antibody detection, has been used widely to diagnose human diseases [18], monitor animal infectious diseases [19], [20], [21], [22], [23], and detect viral antibodies in clinics or laboratories [24], [25], [26], [27], [28], [29]. The distinct advantages of blocking ELISA include high-volume sample testing, applicability across multiple species, and greater objectivity than some traditional techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Blocking ELISA, a specific method for antibody detection, has been used widely to diagnose human diseases [18], monitor animal infectious diseases [19], [20], [21], [22], [23], and detect viral antibodies in clinics or laboratories [24], [25], [26], [27], [28], [29]. The distinct advantages of blocking ELISA include high-volume sample testing, applicability across multiple species, and greater objectivity than some traditional techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Serology is the best tool for detection of clinical and subclinical MG infection in poultry flock [24]. Enzymelinked immunosorbent assay is one of the most widely used serological tests that are broadly used for finding of Mycoplasma gallisepticum (MG) infections [17,25], since ELISA and HI tests only identify IgG antibodies that arise after 7-10 days (DPI) and last for 180 days [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there is no commercial test kit for HI method. The alternative method is the monoclonal antibodybased blocking enzyme-linked immunosorbent assay (blocking ELISA) (Miao et al, 2000;Sun et al, 2 0 0 7 ) but it is mainly used in research. Although blocking ELISA using monoclonal antibody shows high specificity and acceptable sensitivity (Zhang et al, 1999), there are some limitation in testing such as (1) monoclonal antibody have only for Page serovar A and C (2) monoclonal antibody are not commercial available ( 3) some isolates of A. paragallinarum do not react with monoclonal antibody (Blackall, 1999).…”
Section: Importance and Rationalementioning
confidence: 99%
“…Uncertainty of testing results depends on individual skills and method of preparation. The alternative method is monoclonal antibody-based blocking enzyme-linked immunosorbent assay (blocking ELISA) (Miao et al, 2000;Sun et al, 2007) which is highly specific with acceptable sensitivity (Zhang et al, 1999). They reported that the sensitivity of blocking ELISA against infectious coryza for serovar A and serovar C were 78.7% and 64.7%, respectively, and the specificity of blocking ELISA against infectious coryza for serovar A and C were 99.…”
Section: Serological Detectionmentioning
confidence: 99%